The Silencing of Female Bodies during the Indian Partition and Female Agency in Postcolonial Pakistan: Analysis of Bapsi Sidhwa’s Ice-Candy-Man - Ghilzai, Shazia Akbar; Shahnaz, Ambreen; Suleman, Nazia (Pakistan Journal of Humanities and Social Sciences, 2024)
This research paper analyzes Bapsi Sidhwa's novel Ice-Candy-Man which explores the effect of the Indian Partition on female bodies. It focuses on how the Partition silenced female voices, how it altered female identities, and how women were left powerless in the face of the Partition. It also explores how Sidhwa uses the novel to evoke the struggles of women during this time and how these struggles continue to find resonance today. Additionally, it examines the different themes of oppression, violence, and discrimination that are highlighted in the novel. The study discusses how Sidhwa's novel serves as a powerful reminder of the importance of female representation and autonomy. It provides an insightful look into the effects of partition on postcolonial Pakistan. It explores the role of gender, national culture, and the power dynamics between different communities in India to provide a comprehensive understanding of how partition and its aftermath continue to shape the country. In particular, it examines how violence and communal violence have become entrenched in postcolonial Pakistan. The analysis of Ice-Candy Man provides a unique perspective on the impact of partition on gender and national identities and how these identities are used to perpetuate violence and inequality in Postcolonial Pakistan.